Identifying the antecedents of work-role overload in police organizations - Duxbury, Linda (Criminal justice and behavior, 2015)
This paper describes a three-phase multi-method research initiative to develop and validate measures used to quantify sources of work-role overload in policing. Phase I used qualitative techniques to generate items that predicted work-role overload in policing. These items were used to construct the initial measure and then tested (Phase II) using a sample of 202 police officers from one organization. Phase III tested the unidimensionality, validity, and reliability of the five measures identified in Phase II using a larger survey of 2,755 sworn officers working in 25 police organizations. Exploratory factor analysis identified and confirmatory factor analysis validated five antecedents to work-role overload in policing: competing demands, the court system, pressures to perform work outside one?s mandate, understaffing, and a nonsupportive organizational culture.